Comparison of local ablation with Albendazole or laparoscopic hepatectomy combined with Albendazole in the treatment of early hepatic alveolar echinococcosis - A, Jide; Chai, Jinping; Shao, Zongping; Zhao, Shunyun; Wang, Hao; A, Xiangren; Yang, Jinyu (Frontiers in Public Health, 2022)
Objective: This study attempts to compare the real efficacy of the above treatment methods, so as to find the best treatment for this kind of patients. Methods: The data of patients with hepatic AE who underwent laparoscopic hepatectomy (LH), RFA and MWA in Qinghai Provincial People's Hospital from January 2015 to January 2021 were collected. At the same time, the cases treated with Albendazole ( ABZ ) were collected together with the institution for disease control and prevention. According to the treatment methods, the above cases were divided into LH group, RFA group, MWA group and medication group. The basic data and postoperative recovery indices of the four groups were compared respectively. Results: A total of 199 patients with hepatic AE were enrolled in this study, including 90 males and 109 females. The youngest was 5 years old and the oldest was 66 years old, with an average of 33.41±14.64 years old. 20.6% of the patients had hepatitis B (41/ 199). 45 patients underwent ultrasound-guided RFA, 47 patients underwent ultrasound-guided MWA, 51 patients were treated with ABZ and 56 patients underwent LH. There were no significant differences in baseline characteristics among the four groups (P > 0.05). Then RFA group and MWA group were advantageous than LH group regarding operation time and incidence of postoperative complications (P < 0.05). But recurrence rate of lesion in LH group was significantly lower than RFA group, MWA group and medication group. However, there was no significant difference in recurrence-free survival time among the four groups (P < 0.05). Conclusion: LH has a significant effect in the treatment of early stage hepatic AE, especially in terms of recurrence which was significantly better than LA and medication alone. Follow-up and adherence to albendazole therapy are essential if conservative treatment is to achieve better outcomes.